EVOLUTION OF STRATEGIC APPROACHES TO MOTIVATION OF THE UNIVERSITY TEACHING STAFF - Ashot R. Alaverdov (Moscow Polytechnic University, 2016)
The article is devoted to the problem of updating the motivation policy with regard to the teaching staff of national higher school. The author considers historically existing in our country approaches to the organization of basic and additional wages of teachers, their social support, moral motivation. The article substantiates the need to change these approaches and formulates priorities in this sphere.